2019
DOI: 10.1016/j.proci.2018.06.154
|View full text |Cite
|
Sign up to set email alerts
|

Large scale effects in weakly turbulent premixed flames

Abstract: In this study we numerically investigate large scale premixed flames in weakly turbulent flow fields. A large scale flame is classified as such based on a reference hydrodynamic lengthscale being larger than a neutral (cutoff) lengthscale for which the hydrodynamic or Darrieus-Landau (DL) instability is balanced by stabilizing diffusive effects. As a result, DL instability can develop for large scale flames and is inhibited otherwise. Direct numerical simulations of both large scale and small scale three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Due to their large-scale nature [16], simulations of laminar, intrinsically unstable premixed flames are generally computationally demanding [3]. However, intrinsic instabilities can be effectively investigated in a two-dimensional setting.…”
Section: Datasets Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their large-scale nature [16], simulations of laminar, intrinsically unstable premixed flames are generally computationally demanding [3]. However, intrinsic instabilities can be effectively investigated in a two-dimensional setting.…”
Section: Datasets Descriptionmentioning
confidence: 99%
“…However, intrinsic instabilities can be effectively investigated in a two-dimensional setting. It was shown that large-scale, three-dimensional flames exhibiting hydrodynamic instabilities share most of the morphological features with their two-dimensional counterparts, such as curvature statistics, often used as a marker for such instabilities [16]. These considerations, therefore, justify the choice of a 2D configuration.…”
Section: Datasets Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) for 2D Bunsen flames [25] and recently some of the authors have measured the dispersion relation in a Hele-Shaw cell [17,21]. Numerically some measurements of growth rates have been performed, first for one-step chemistry [9,10,28] and recently for hydrogen-air flames [11,27,29].…”
Section: Linear Regime Analysismentioning
confidence: 99%
“…Identifying the instability in a turbulent environment is not as straightforward, because fluctuations of the flame surface resulting from the turbulence are interlaced with disturbances caused by gas expansion, making the distinction difficult even at relatively low intensities. A number of experimental studies (Paul & Bray 1996;Kobayashi, Kawabata & Maruta 1998;Savarianandam & Lawn 2006;Troiani, Creta & Matalon 2015;Bauwens, Bergthorson & Dorofeev 2017) and simulations (Akkerman & Bychkov 2003;Creta, Fogla & Matalon 2011;Creta et al 2016;Fogla et al 2015Fogla et al , 2017Yu, Bai & Bychkov 2015;Lapenna et al 2019) have provided insight on the effect of the DL instability on turbulent flames. More recent studies including DNS for Bunsen flames (Klein, Alwazzan & Chakraborty 2018;Lapenna et al 2019Lapenna et al , 2021Zhang et al 2019;Rasool, Chakraborty & Klein 2021) have shown an interplay between the underlying turbulent field and the flame region under different pressures and Lewis number conditions, highlighting the role that DL instability plays in modifying flame topologies, surface curvature, impact on flame stretch and consumption speed.…”
Section: Introductionmentioning
confidence: 99%